Impact of dehydroepiandrosterone (DHEA) supplementation on testosterone concentrations and BMI in elderly women: A meta-analysis of randomized controlled trials. (January 2021) - Hu, Ying; Wan, Ping; An, Xiaoqing; Jiang, Guilin
Highlights: Overall results demonstrated that testosterone levels increased significantly after DHEA administration in elderly women. DHEA administration significantly decreased BMI. DHEA administration significantly increased LBM. Abstract: Background: Despite the fact that numerous clinical studies have evaluated the positive effects of dehydroepiandrosterone (DHEA) supplementation on testosterone concentrations and on the body mass index (BMI), more evidence is needed to certify that DHEA is a BMI-reducing agent in the elderly. This meta-analysis aims to clarify the various incompatible results and investigate the impact of DHEA supplementation on serum testosterone levels and lean body mass in elderly women. Methods: Four scientific databases (EMBASE, PubMed/MEDLINE, Scopus and Web of Science) were searched from inception until 20 August 2020 for trials comparing DHEA with placebo. Results were presented as weighted mean differences (WMDs) and 95 % confidence intervals (CIs) based on the random effects model (DerSimonian-Laird approach). Results: Nine arms with 793 subjects reported testosterone as an outcome measure. The overall results demonstrated that testosterone levels increased significantly after DHEA administration in elderly women (WMD: 17.52 ng/dL, 95 % CI: 6.61, 28.43, P = 0.002). In addition, DHEA administration significantly decreased the BMI (WMD:-0.39 kg/m 2, I 2 = 0.0 %). Conclusion: The results of the current meta-analysis support the use of DHEA supplementation for increasing testosterone concentrations in elderly women.